Quality of care provided to newborns by nursing personnel at BP Koirala Institute of Health Sciences - Shrestha, M; Singh, R; Upreti, D (Kathmandu University Medical Journal, 2010)
Background: Birth is a major challenge for the newborn to negotiate successfully from intrauterine to extra uterine life. The first few hours since birth is the most crucial period in the life of an infant for further growth and development, which is largely determined by the quality of care that the newborn receives. Objective: The aim of this study is to assess the quality of care provided by nursing personnel to newborn in the labour room. Materials and methods: This study was conducted in BP Koirala Institute of Health Science. Cross sectional, non participatory observational research design was adopted for the study. Care provided by nursing personnel to 814 normal newborns was observed. Samples were chosen by non probability purposive sampling technique. Data was collected through observational method by trained nursing personnel, using 46 items pre-tested, validated and self developed observational checklist. Care provided to newborns was observed from birth to two hours and categorised as good, average and poor based on scores obtained. Data was entered and analysed using SPSS-10. Descriptive statistics- [Mean, percentage, frequencies and standard deviation] was used to describe the quality of care provided to the newborn babies. Results: Overall quality of care was good in 42.36%, average in 57.64% and none of them received poor care. Overall mean score for quality of care was 34.75/46 (75.54 %). Regarding subscales quality of care was good in majority of newborns in areas such as Preparation to receive the baby (76.1%), Initiation of breathing (100%), Maintaining thermoregulation (77.3%), Physical assessment (90.9%), and other aspects of care (95.2%). However the quality of care was poor in majority of newborns in establishment of breast feeding (58.23%) and average in prevention of infection (76.9%). Conclusion: Study findings highlight the need for focus in establishment of breast feeding and prevention of infection. Key words: Quality of care; newborns; nursing personnel; breast feeding; prevention of infection and assessment of newborn. DOI: 10.3126/kumj.v7i3.2729 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 231-237